2010
DOI: 10.1271/bbb.90459
|View full text |Cite|
|
Sign up to set email alerts
|

Poly(3-hydroxybutyrate) Production by IsolatedHalomonassp. KM-1 Using Waste Glycerol

Abstract: Biodiesel fuel is favored as a type of carbon neutral energy. To popularize its usage, by-product waste glycerol utilization is a critical problem. We tried to isolate waste glycerol utilizing bacteria, and obtained the alkalo-and halophile bacteria Halomonas sp. KM-1. This strain produced bioplastic poly(3-hydroxybutyrate) (PHB) in a simple medium and diluted waste glycerol as a sole carbon source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 10 publications
1
44
0
3
Order By: Relevance
“…Among these, the lowest Mn PHAs was derived from Halomonas sp. KM-1 cultivated in a medium supplemented with 3% of waste glycerol at 29 9 10 3 g mol -1 [20]. Some researchers have published data that we will compare with our observation.…”
Section: Gel Permeation Chromatographysupporting
confidence: 69%
See 1 more Smart Citation
“…Among these, the lowest Mn PHAs was derived from Halomonas sp. KM-1 cultivated in a medium supplemented with 3% of waste glycerol at 29 9 10 3 g mol -1 [20]. Some researchers have published data that we will compare with our observation.…”
Section: Gel Permeation Chromatographysupporting
confidence: 69%
“…Differing from the other carbon sources that have been studied for PHAs biosynthesis, both pure and crude glycerol used as carbon sources for PHAs production were reported with significantly low Mw PHAs because of glycerol esterification of PHAs resulting in chain termination (end-capping) [5,45]. It has been reported that the PHAs produced from biodieselbased glycerol showed Mw ranging from 786 9 10 3 to 87 9 10 3 g mol -1 and Mn ranging from 215 9 10 3 to 29 9 10 3 g mol -1 for different types of microorganisms and culture conditions [4,5,8,20,21,23]. Among these, the lowest Mn PHAs was derived from Halomonas sp.…”
Section: Gel Permeation Chromatographymentioning
confidence: 99%
“…Under such conditions, glycerol is generally converted into P(3HB) by various native PHA producing bacteria. 5,[83][84][85][86][87] As shown in Figure 3, glycerol is converted to glyceraldehyde-3-phosphate (GAP) by three enzymes, glycerol kinase (GlpK), glycerol-3-phosphate dehydrogenase (GlpD), and triosephosphate isomerase (TPI). GAP is an intermediate in the glycolysis pathway and eventually metabolized to pyruvate.…”
Section: Production and Characterization Of Polyhydrox-yalkanoates Frmentioning
confidence: 99%
“…KM-1 (Kawata and Aiba, 2010), osmophilic organism (Koller et al, 2005), Pseudomonas oleovorans NRRL B-14682 and Pseudomonas corrugata 388 (Ashby et al, 2004) from different sources of biodiesel feedstock. Among these, in small scale cultivation, H. hydrothermalis could accumulate PHB content up to 75.8% of the cell dry weight (CDW) with 3 g/L PHB concentration by using mineral salt medium (MSM) supplemented with 2% (w/v) of 95% glycerol content from Jatropha biodiesel byproduct (Shrivastav et al, 2010) In Thailand, as the biodiesel industry grows, research study for biodiesel-derived waste glycerol conversion into useful product should be done in order to minimize the environmental problem caused by this waste stream.…”
Section: Introductionmentioning
confidence: 99%